California Power Crisis : Lessons for Developing Countries - World Bank (Washington, DC, 2014)
California introduced competition to its retail and wholesale power markets in 1998, but has experienced a major crisis during 2000 and into 2001. The paper attempts to gain an understanding of what has happened in California, and to draw lessons from the California experience that are applicable to other countries. The paper begins with an overview of the key features of the 1998 California power sector reform: how it differs from reforms elsewhere, the events and actions that have put it in a crisis mode, and the main lessons that can be learned from the crisis. The main text is divided into two parts. Part I discusses in depth lessons learned, which concern mainly the establishment and regulation of a mandatory, wholesale power market based on spot pricing. Since this is not a near-term option for many developing countries, the paper also describes other, more-limited forms of competition that may suit their situations. Part II details the specific reforms initiated in California, reviews the factors that led to the crisis, and examines whether the crisis could have been avoided through better market design and management.